노인의 신체활동과 주관적건강인식의 관련성 - 정은선 (The Graduate School, Ajou University, 2013)
Abstract Association Between Physical Activity and Self-Reported Health in Korean Older Adults Eun-Seon Jeong Graduate School of Public Health Ajou University (Supervised by Professor Yunhwan Lee, M.D., Dr.P.H.) The purpose of this study was to examine the association between physical activity and self-assessed health among older Koreans. This study is implemented to find out the relationship between demographic factors and health related factors considered as the factors related to the subjective health perception of the elderly and analyze the result to facilitate as the base data to forecast the physical activity program of the elderly that is appropriate to the level of subjective health perception. The data used in the research is the date with the representative features on the elderly with 65 years and older who are residing in local communities from the first year of the Fifth National Health and Nutrition Survey of 2010 and the statistical analysis was made on 1,338 subjects with SPSS version 19.0. With respect to the analysis method, the chi-square verification and the logistic regression analysis are facilitated. As a result of the study, when the demographic factors and health related factors of the elderly are controlled, it shows the meaningful relativity on the physical activities and subjective health perception by the elderly. The subjective health perception by the elderly has noticeable difference depending on the recommended exercise, muscle exercise, gender, household income, education level, occupation, marital status, single status, chronic illness, stress perception rate, and depression experience. In other words, there is a tendency of looking into one’s health condition more pessimistically as not practicing recommended exercise, not practicing muscle exercise, for female, for low household income, for low education level, for having no occupation, for having no spouse, for single status, for person with chronic illness, for having higher stress perception rate, for having the smoking habit and for having depression experience. In particular, when considering the fact that recommended exercise and muscle exercise make important influence on the health perception assessment, it is expected to increase the activities of persons performing recommended exercise and muscle exercise along with enhancement in the subjective health perception. In future, effort has to be made to increase the bodily activities with enhancement in the subjective health perception on the basis of more diversified factual analysis and multi-phased research. Key words: Aged, physical activity, self-reported health
학위논문(석사)아주대학교 보건대학원 :보건학과,2013. 2
Keywords: 노인의 신체활동; 주관적건강인식; 관련성